2019
DOI: 10.1177/1473225419890691
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Children’s Court Processes and Decisions: Perceptions of Children and Their Families

Abstract: This article presents preliminary findings regarding children’s and families’ experiences of Children’s Court proceedings in which they are participants. The findings come from a systematic review of Australian and international qualitative literature in relation to how children and their families perceive and understand these court processes. The review reveals that we know little about children’s and parents’ perspectives. However, their insights are vital so that courts can reasonably address issues and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…These views concur with previous research on perceptions of courts. Saunders et al (2020) in a meta-synthesis found that children and parents felt alienated by courts and experienced the court process as too technical and distressing.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These views concur with previous research on perceptions of courts. Saunders et al (2020) in a meta-synthesis found that children and parents felt alienated by courts and experienced the court process as too technical and distressing.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Children Experiences of the Child Justice System… ~ 3 ~ Children courts are established by the children act, ( 2022), yet there are only two in the country that can fit the basic criteria of a child friendly court. In the rest of the country, adult courts are cleared for children matters with the alternative being having the cases heard in the magistrate's chambers (Wangamati et al, 2019) In a systematic review of literature children and families understanding of court processes, Saunders et al (2020), found that most children had no idea what was going on even though they were physically present in court because no one simplified the process for them. Studies show that children's experiences of probation officers play a role in their compliance to the conditions of probation (Fine et al, 2019).…”
Section: Muema Et Almentioning
confidence: 99%
See 2 more Smart Citations